(untitled) (Global Journal of Management and Business Research, 2015)
It is an unquestionable fact that gross domestic saving is one of the most contributing factors of economic growth of a nation. It plays concrete role in fostering investment, production, employment and eventually the economic growth. The present paper endeavors to analyze and exemplifies the contributions of household sector, private corporate sector and public sector in Gross Domestic Savings (GDS) and thus Gross Capital Formation (GCF) of India. The study is based on secondary data from 2000-2013. The statistical tools like Percentage, ANOVA, Correlation and Regression analysis are used for data analysis. The analysis divulges that the maximum contribution to GDS and GCF is made by household sector followed by private corporate sector and then public sector.